AVERAGE NEUTRON CROSS- SECTION MEASUREMENT FOR SOME (n,p) REACTIONS USING NEUTRON GENERATOR AND 241AmBe NEUTRON SOURCE - S. M. Al-jobori; M. Ahmed Ulaiwi; Saad Saleh Dawod; A. H. Murbat (Journal of Madenat Alelem University College, 2010)
The (n,p) reaction cross-section was measured for the reactions 27Al (n,p)27Mg, 24Mg(n,p)24Na, 58Ni(n,p)58Co, 56Fe(n,p)56Mn, 52Cr(n,p)V52and 28Si(n,p)28Al using the 241AmBe neutron generator as a neutron source. Also the average neutron cross-section has been determined for the above reactions. High purity powder materials and foils were used in this study as pelts of 1.6 mm diameters. The neutron activation technique has been used for irradiation and measurement. Well type 3״3×״ Sodium Iodide Scintillation Detector has been used for Gamma radiation detection with MCA. The average (n,p) reaction cross-section has been determined relative to the reaction 27Al(n,p)27Mg for short half life products. While the cross-section of the 27Al (n,α)24Na reaction was used as a relative standard for medium and long half-life products. The Gamma absorption has been taken into account using DSAC computer program.